The Legal Framework Governing Restrictions on the Right of Access to Information - Kazem Hanoun, Researcher. Hoda; Muhammad Abd, Prof.Dr. Aqeel; Zaki Nouri, Assist. Prof. Soha (Basra studies journal, 2025)
The right to access information is one of the fundamental human rights through which society can achieve transparency and promote democracy. However, this right cannot be fully realized unless it is constitutionally and legally regulated in a manner that fulfills the purpose for which it was established. It is important to note, however, that this right is not absolute. Various restrictions have been imposed to safeguard the public interest most notably, to protect national security and the integrity of legal proceedings. At times, limitations are also imposed to preserve private interests, such as the protection of personal privacy and the confidentiality of professional secrets